Class D amplifier power stage with PWM feedback loop - Lam, C.K.; Tan, M.T.; Cox, Stephen M.; Yeo, K.S. (IEEE, 2013)
This paper presents a Second-Order Pulse Width Modulation (PWM) feedback loop to improve Power Supply Rejection (PSR) of any open-loop PWM Class-D amplifiers (CDAs). PSR of the audio amplifier has always been a key parameter in mobile phone applications. In contrast to Class AB amplifiers, the poor PSR performance has always been the major drawback for CDAs with half-bridge connected power stage. The proposed PWM feedback loop is fabricated using GLOBALFOUNDRIES' (GF’s) 0.18 µm CMOS process technology. The measured PSR is more than 80 dB and the measured Total Harmonic Distortion (THD) is less than 0.04% with a 1 kHz input sinusoidal test tone.